2007
DOI: 10.1088/0953-8984/19/36/365223
|View full text |Cite
|
Sign up to set email alerts
|

Structural properties of nanometre-sized ZnO crystals doped with Co

Abstract: Nanometre-sized ZnO crystals doped with Co were synthesized by a co-precipitation method combined with a thermal treatment. By changing the reaction temperature, we can control the crystallite size from roughly 10 nm particles to 20 nm × 200 nm nm rods grown along the hexagonal c-direction. X-ray diffraction and Raman scattering showed growth of high-quality wurtzite ZnO crystals incorporating Co systematically in the ZnO host lattice in the tested range of [Co]<3.0 mol%. Electronic transitions of Co in the ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 34 publications
(35 reference statements)
1
11
0
2
Order By: Relevance
“…Thus, we apprehend that this Raman peak at ∼660 cm −1 did not originate from possible partial formation of Mnrich solid solution layer in the Mn:ZnO nanorods or precipitation of ZnMn 2 O 4 . Rather, this peak might have originated from the combined effect of two-phonon signal of ZnO as indicated by Calleja and Cardona [32] and Hasuike et al [33] and the vibration mode of Mn-O as observed by Xu et al [29].…”
Section: Raman Analysismentioning
confidence: 86%
“…Thus, we apprehend that this Raman peak at ∼660 cm −1 did not originate from possible partial formation of Mnrich solid solution layer in the Mn:ZnO nanorods or precipitation of ZnMn 2 O 4 . Rather, this peak might have originated from the combined effect of two-phonon signal of ZnO as indicated by Calleja and Cardona [32] and Hasuike et al [33] and the vibration mode of Mn-O as observed by Xu et al [29].…”
Section: Raman Analysismentioning
confidence: 86%
“…In previous report [13], ZnO nanocrystals doped with Co with the dimension of 10 nm were successfully synthesized by co-precipitation method, and Co ions were systematically substituted in Zn sites.…”
mentioning
confidence: 99%
“…method with post-thermal treatment at 70 °C [13]. All the samples had wurtzite structure of ~10 nm, regardless the Co doping level, and secondary products such as precipitates of Co or its oxide were not present.…”
mentioning
confidence: 99%
“…La figura 9 muestra del espectro de absorbancia de las películas de Zn1-xAuxO, en la cual se observa una gran absorción por parte del ZnO a las temperaturas de recocido de 400 °C, 500 °C y 600 °C; coincidiendo con el trabajo realizado por Hasuike et al (2007). Se observa un pequeño aumento en la absorción óptica a medida que incrementa la temperatura de recocido; esto se debe a que en el ZnO a mayores temperaturas hay una disminución de defectos puntuales del tipo Schottky, o defectos catiónicos (metal-deficiente), quienes a la vez generan una disminución de la brecha energética, como referencian los autores Al-Ghamdi et al (2013) y Dilonardo et al (2016.…”
Section: Propiedades óPticasunclassified